Vietnam Vzdálený I Blízký : Potomci Vietnamců V Česku. - Svobodová, Andrea. (SLON - Studie Series, 2024)
The book 'Vietnam vzdálený i blízký' by Andrea Svobodová delves into the life stories of Vietnamese descendants living in the Czech Republic. Through narrative analysis, it explores the complex social spaces these individuals navigate, which span between Vietnam and the Czech Republic. The book examines how these young people are influenced by multiple political, economic, and social systems, leading to diverse cultural practices, identities, and experiences. It addresses the integration of Vietnamese culture into their lives and questions the role of ethnicity in identity formation. Aimed at scholars and readers interested in migration studies, the book is grounded in Svobodová's extensive experience in social anthropology and geography, providing insights into the integration of migrants and their descendants.